Factors influencing nutritional status of 6-59 months children at primary health care centre in Chapagaun VDC of Lalitpur District. - Shrestha,Sushan Man (2009)
Summary: Under nutrition is serious problem of developing countries like Nepal as it influences the survival, growth and development of child. Under nourished child are more likely to die from childhood disease than those who were well nourished. It is estimated that about one sixth of the mortality of the entire disease burden in the developing countries is attributed to underweight. The report from recent DHS 2006 showed the prevalence of stunted, wasted and underweight children is very high constituting 49 percent, 13 percent and 39 percent respectively. This study aimed to analyze the factors influencing nutritional status of 6-59 months children at Primary Health Care Centre in Chapagaun VDC of Lalitpur district of Nepal. The general objective of the study is to find out the nutritional and its relationship with factors among the children under-five at PHC in Chapagaun VDC of Lalitpur District. This is a cross-sectional study, conducted on sample size of 180 mothers who were interviewed and their height and weight were taken. Similarly the anthropometric measurements of their children aged 6-59 months were also taken. The data were collected using semi-structured questionnaire translated into Nepali language. Data were processed and analyzed using SPSS 11.5 and EpiInfo-6. Descriptive, bivariate analysis and logistic regression was applied to analyze the association of factors with the nutrition status of children. Nutritional status of children was represented by stunting, wasting and underweight, which were considered as the criteria recommended by WHO and NCHS. Those children were considered as under nourished whose value for height for age, weight for height and weight for age were below two standard deviation (<-2SD) from the reference median value. Among mothers 69.7 percent were at the age group 20-29 years of age. Newar dominates the ethnicity among the mothers. Almost 90 percent of the mothers were Hindu. Only 11.7 percent mothers were illiterate but the education level SLC and above among mothers were 36.1 percent. Housewife dominates the occupation with 38.9 percent where as 48.9 percent fathers were service holders. Nuclear type family observed in 64.4 percent of the respondents. The average family size found was 5 people per household. Almost similar distribution was observed among the sex of the children with 53.9 percent of male. The prevalence of stunting, wasting and underweight observed were 45.6 percent, 8.3 percent and 26.1 percent along with 15 percent, 1.1 percent and 4.4 percent severe stunting, severe wasting and severe underweight respectively. Among the children 88.7 percent received Vitamin A capsule during last six months. Similarly 85.9 percent children received deworming tablet in past six months. All children had complete immunization status. It was reported that 6.7 percent, 8.9 percent had diarrhea and cough and cold respectively. Similarly it was reported that 5.6 children were admitted to hospital during last year. It was found that 91 percent of the mothers initiated the breast feeding to the child within one hour of the birth of the child and 93.3 percent gave colostrums to their children. The proportion of currently breast feeding were 47.7 percent among them 4.4 percent of them were exclusively breast fed. It was found that 17.8 percent of the mothers were underweight where as 58.9 percent was in the category normal. The proportion of overweight and obese were found to be 23.3 percent. The average age of mothers was found to be 28.2 years with standard deviation of 4.80 years. Similarly the mean age of mothers at marriage and the mean age of mothers at first child were found to be 21.54 and 23.22 years with standard deviation of 3.02 and 3.07 years respectively. Stunting status of the children was found significantly related with education level, earning status, occupation, ethnicity and religion of mothers and status of child had diarrhea in last two weeks. Similarly wasting status of the children was found significantly related with type of family, the time of initiation of breast feeding to the child immediately after birth, status of colostrums given to the child after birth and recent breast feeding status. Where as underweight status the children was found significantly related with ethnicity, type of family, religion, the time of initiation of breast feeding to the child immediately after birth, status of colostrums given to the child after birth and recent breast feeding status and status of child receiving Vitamin A capsule during past six months. In this study, though the factor like education level, earning status, occupation, ethnicity and religion of mothers, type of family, the time of initiation of breast feeding to the child immediately after birth, status of colostrums given to the child after birth and recent breast feeding status and status of child receiving Vitamin A capsule during past six months and status of child had diarrhea in last two weeks shows significant association with the nutritional status of the child in bi-variate relationship, logistic regression suggested that only ethnicity and occupation of mother type of family, time of initiation of breast feeding and status of given colostrums, breast feeding status and status of diarrhea in child in the last two weeks had significant association with nutritional status of child.